2015
DOI: 10.1158/1078-0432.ccr-14-3334
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Candidate Gene Panel for the Early Diagnosis of Prostate Cancer

Abstract: Purpose: Serum PSA (sPSA) testing has led to the identification of patients with indolent prostate cancer, and inevitably overtreatment has become a concern. Progensa PCA3 urine testing was shown to improve the diagnosis of prostate cancer, but its diagnostic value for aggressive prostate cancer is limited. Therefore, urinary biomarkers that can be used for prediction of Gleason score !7 prostate cancer in biopsies are urgently needed.Experimental Design: Using gene expression profiling data, 39 prostate cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
163
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 203 publications
(172 citation statements)
references
References 33 publications
6
163
0
3
Order By: Relevance
“…Indeed, targeted cancer panels are currently most commonly used as diagnostic and prognostic tools in clinical oncology due to their advantages such as low cost and relatively simple interpretation [45,46]. Breast cancer (BC) is a good example of the application of NGS as an effective method to increase the detection rate of high-risk cases [47]. Previous studies have shown that BRCA1 and BRCA2 mutations cause about 30% of BC cases.…”
Section: Advantages Of Ngs Technologiesmentioning
confidence: 99%
“…Indeed, targeted cancer panels are currently most commonly used as diagnostic and prognostic tools in clinical oncology due to their advantages such as low cost and relatively simple interpretation [45,46]. Breast cancer (BC) is a good example of the application of NGS as an effective method to increase the detection rate of high-risk cases [47]. Previous studies have shown that BRCA1 and BRCA2 mutations cause about 30% of BC cases.…”
Section: Advantages Of Ngs Technologiesmentioning
confidence: 99%
“…The HOXC6 and DLX1 homeobox genes are upregulated in prostate cancer cells and their expression increases during the progression of cancer to a higher-grade, castration-resistant and metastatic stage (55,56). The Mi-Prostate Score combined the expression signatures of urine ERG-TMPRSS2 and PCA3 with serum PSA, may improve the prediction of cancer risk and high-grade cancer following biopsy (57).…”
Section: Non-invasive Genetic Biomarker Testmentioning
confidence: 99%
“…Одна из них включала гены РСА3, ELF3, SPP1 и HIST1H2BG, другая -PCA3 и TMPRSS2: ERG с ис-пользованием Progensa и новой тест-системы Т2ERG (Hologic), еще в одной работе анализировали экспрес-сию 12 генов [26][27][28]. Опубликованы панели экспрес-сионных маркеров без РСА3, также направленные на диагностику РПЖ по осадку мочи, которые вклю-чают гены DLX1 и HOXC6 [29][30][31].…”
Section: сравнительный анализ экспрессии гена рса3: а -Roc-анализ эксunclassified